2020
DOI: 10.1177/1948550620971086
|View full text |Cite
|
Sign up to set email alerts
|

Unjustifiably Irresponsible: The Effects of Social Roles on Attributions of Intent

Abstract: How do people’s social roles change others’ perceptions of their intentions to cause harm? Three preregistered vignette-based experiments ( N = 788) manipulated the social role of someone causing harm and measured how intentional people thought the harm was. Results indicate that people judge harmful consequences as intentional when they think the actor unjustifiably caused harm. Social roles were shown to alter intention judgments by making people responsible for preventing harm (thereby rendering the harm as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…In attempting to discern the mechanisms underlying the SEE, some previous empirical work has shown that factors relating to the agent can moderate it (Cova, Lantian, & Boudesseul, 2016), such as personality, motives, and past behaviour (Brogaard, 2010;Hughes & Trafimow, 2012, 2015Shepherd, 2012), level of power (Robbins et al, 2017), skill (Guglielmo & Malle, 2010b), goodness or badness (Beebe & Jensen, 2012;Newman, De Freitas, & Knobe, 2015), contextual constraints on the agent (Monroe & Reeder, 2011), and social role (Rowe, Vonasch, & Turp, 2020). Participants may also strongly consider the agent's "I don't care" statement in representing the agent's attitudes (Sripada & Konrath, 2011) as it communicates an active and negative desire (Guglielmo & Malle, 2010a).…”
Section: Methodsmentioning
confidence: 99%
“…In attempting to discern the mechanisms underlying the SEE, some previous empirical work has shown that factors relating to the agent can moderate it (Cova, Lantian, & Boudesseul, 2016), such as personality, motives, and past behaviour (Brogaard, 2010;Hughes & Trafimow, 2012, 2015Shepherd, 2012), level of power (Robbins et al, 2017), skill (Guglielmo & Malle, 2010b), goodness or badness (Beebe & Jensen, 2012;Newman, De Freitas, & Knobe, 2015), contextual constraints on the agent (Monroe & Reeder, 2011), and social role (Rowe, Vonasch, & Turp, 2020). Participants may also strongly consider the agent's "I don't care" statement in representing the agent's attitudes (Sripada & Konrath, 2011) as it communicates an active and negative desire (Guglielmo & Malle, 2010a).…”
Section: Methodsmentioning
confidence: 99%